Interaction between Territorial Capital and Family Businesses - Csilla Polster; Márta Konczosné Szombathelyi (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
The purpose of the study is to investigate the interaction between the territorial capital of a region and the family businesses operating there. In order to obtain a comprehensive picture about the interaction between family businesses and certain elements of territorial capital. On one hand, the study is based on the scientific literature of research areas and the previous research. On the other hand, two business studies are demonstrated based on deep interviews with the successors of the family businesses. The study gives an example of the social and cultural impacts of territorial capital on family businesses and the growing power of family businesses in terms of territorial capital. There is a strong interaction between corporate regional involvement and embedding and territorial capital.
Keywords: M21; 330; territorial capital; family businesses; embedding; interaction